Relationship between Osteoporosis and Periodontitis in the Females over 40 Years - A Haerian-Ardakani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2014)
Introduction: Osteoporosis and periodontitis are types of diseases that their prevalence increases with age and bone loss is one of the common features of these two diseases. Therefore, the purpose of this study was to evaluate the relationship between bone mineral density and periodontitis in females over 40 years Methods: In this cross-sectional study, 333 females were enrolled for osteoporosis to be assessed among women who referred to a bone densitometry center of Khatamolanbya clinic in Yazd and applied for BMD (Bone Mineral Density) according to their physician's diagnosis of osteoporosis. The study participants were required to meet the age criteria, have at least ten teeth, and not to undergo any treatment for osteoporosis. Periodontal examinations were performed after densitometry including Clinical Attachment Loss (CAL), Bleeding on Probing (BOP), Probing Depth (PD). Then, data were analyzed utilizing SPSS software via chi-square test. Results: Generally, mean of BOP, PD, CAL in osteoporotic subjects were significantly more compared to normal and osteopenic ones, though no significant difference was observed between osteopenic and normal. Moreover, in premenopausal women, there was a significant difference in regard with CAL indicator in osteoporotic patients compared to normal controls. Conclusion: Osteoporotic subjects showed more severe periodontitis than normal and osteopenic subjects. However, osteopenic and BMD normal subjects showed no significant difference in CAL mean. As a result, this could reveal the importance of early diagnosis of BMD decrease before it can affect periodontal tissues.